2017
DOI: 10.20959/wjpps20175-9203
|View full text |Cite
|
Sign up to set email alerts
|

Overview on L-Asparaginase

Abstract: L-asparaginase is a potential anti-tumour enzyme that is known for its ability to reduce the amount of L-asparagine necessary for the tumor cells. It has been used against acute lymphoblastic leukemia and lymphosacoma. This review includes methods for isolation and screening of potential microbes for mass production of enzyme. The clinical use of L-asparaginase has been highlighted. Methods of strain improvement that can increase the efficiency of selected strains have also been described. Further sttempts hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Prokaryotic L-asparaginase is ecologically involved in transformation of organic nitrogen to release ammonia via the ammoni cation process [18]. Nitrogen rich compounds, peptides and amino acids are among available nitrogen sources in aquatic habitats where type II secretory L-asparaginase can be utilized for scavenging nitrogen by a range of prokaryotes [18,19]. The secretory L-asparaginase act as a public good; providing surrounding cells by nitrogen source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prokaryotic L-asparaginase is ecologically involved in transformation of organic nitrogen to release ammonia via the ammoni cation process [18]. Nitrogen rich compounds, peptides and amino acids are among available nitrogen sources in aquatic habitats where type II secretory L-asparaginase can be utilized for scavenging nitrogen by a range of prokaryotes [18,19]. The secretory L-asparaginase act as a public good; providing surrounding cells by nitrogen source.…”
Section: Resultsmentioning
confidence: 99%
“…One major limitation of this approach is due to cultivation bottleneck; majority of prokaryotes (up to 99%) are still evading the bound of culture [17], consequently; their novel genetic contents remain inaccessible. Additionally, prokaryotes represent selective expression for different types of L-asparaginases under certain environmental condition [18,19], thus further limiting the culture/expression-dependent screening approaches. For example, model organism E. coli's type I Lasparaginases is a cytoplasmic low-a nity protein continuously expressed and required for growth, whereas its type II enzyme is periplasmic with high-a nity toward L-asparagine, expressed under anaerobic and starvation conditions acting as a scavenger to absorb nitrogen from the environment [18].…”
mentioning
confidence: 99%
“…However, few studies used lactose for Actinobacterial Lasparaginase production. Furthermore, the nitrogen sources used during fermentation has an impact on L-asparaginase production [1,2,19]. El-naggar et al [25] suggested that Lasparaginase activity increases with the concentration of L-asparagine in the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a high demand for oncolytic enzymes because cancer cells are more sensitive to them [2]. L-asparaginases produced by microorganisms and plants have been studied, and several attempts have been made to increase their activity [9][10][11][12] using different experimental designs, such as the Box-Behnken [13] and Plackett-Burman [12] methods.…”
Section: Survival In Pediatric Patients With All Has ----------------mentioning
confidence: 99%
See 1 more Smart Citation